Pemanfaatan Pengindraan Jarak Jauh Terhadap Pemetaan Sebaran Klorofil Di Perairan Belawan - Alaudin Alaudin; Iksan Zakiya; Burhanis Burhanis; Roni Arif Munandar; Muammar Kadhafi (Departemen Teknik Kelautan Universitas Hasanuddin, 2024)
Chlorophyll-a is one of the important water quality parameters in the sea. This research was conducted in April 2022 in the Belawan Waters of North Sumatra Province with the aim of knowing the level of chlorophyll-a concentration in these waters. The method used is survey and extraction of Aqua MODIS satellite image data into ASCII data and image data using the seaDAS application. The value of chlorifyll-a concentration obtained in Belawan waters is 3.35-5.91 mg / m³ and has an average value of about 4.65 mg / m³. Belawan waters in April 2022 experienced high chlorophyll-a concentrations.